Revolution in the making of the modern world social identities, globalization, and modernity - Foran, John; Lane, David Stuart; Zivkovic, Andreja (Routledge, 2008)
Featuring contributions from leading thinkers on revolution, this work combines theoretical concerns with case studies of individual revolutions to question whether ideas of revolution are still relevant in the postmodern and globalized world of the twenty-first century. It is suitable for students and scholars of comparative politics, and others.